Super Twisting Sliding Mode Control for PV-Battery Integrated DC Microgrids - Fenniche Abdennour (University of Msila, 2025)
This research addresses the control of a battrey energy storage system integrated with a photovoltaic (PV) source within a DC microgrid, focusing on voltage stabilization and disturbance rejection. Accurate modeling of both the PV generator and battery system was conducted, laying the groundwork for control design and system analysis. A conventional Proportional-Integral (PI) controller was implemented as a baseline. While it performed adequately under steady conditions, it lacked robustness during transient disturbances and rapid system changes. To overcome these limitations, a Super-Twisting Sliding Mode Control (ST-SMC) strategy was introduced, known for its fast convergence and reduced chattering effects . The comparative analysis revealed that the super-twisting control significantly improved voltage regulation and system resilience against disturbances and load variations. The hybrid storage system, under this advanced controller, exhibited superior dynamic response and operational stability . In conclusion, the study emphasizes the necessity of combining accurate system modeling with robust control techniques for reliable renewable energy integration. Future work could focus on real-time implementation, hardware-in-the-loop testing, and the inclusion of additional renewable sources such as wind energy or supercapacitors. Keywords
Keywords: Photovoltaic source (PV); Battrey energy storage system; DC microgrid; Super-Twisting Sliding Mode Control (ST-SMC); Disturbance rejection; voltage stability; power balance; roubustness to system uncertainties.